2017
DOI: 10.3390/ijms18071533
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Phosphatidylinositol 3-Kinase (PI3K) Enhances Ethylene Biosynthesis and Accelerates Flower Senescence in Transgenic Nicotiana tabacum L.

Abstract: Phosphatidylinositol 3-kinase (PI3K) is a key enzyme that phosphorylates phosphatidylinositol at 3’-hydroxyl position of the inositol head group initiating the generation of several phosphorylated phosphatidylinositols, collectively referred to as phosphoinositides. The function of PI3K in plant senescence and ethylene signal transduction process was studied by expression of Solanum lycopersicum PI3K in transgenic Nicotiana tabacum, and delineating its effect on flower senescence. Detached flowers of transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Decreased LOX activity resulted in the decreased lipid peroxidation which can be visualized by the increased membrane stability index in the tissue samples from cytokinin treated scapes. This decrease in the LOX activity and LPO by cytokinin treatment can be attributed to maintenance of adequate phospholipids, proteins and thiols by preventing the leakage of proteases from vacuoles into the cytoplasm (Fukuchi-Mizutani et al 2000;Pak and van Doorn 2005;Liu et al 2016b;Dek et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased LOX activity resulted in the decreased lipid peroxidation which can be visualized by the increased membrane stability index in the tissue samples from cytokinin treated scapes. This decrease in the LOX activity and LPO by cytokinin treatment can be attributed to maintenance of adequate phospholipids, proteins and thiols by preventing the leakage of proteases from vacuoles into the cytoplasm (Fukuchi-Mizutani et al 2000;Pak and van Doorn 2005;Liu et al 2016b;Dek et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Cytokinins have been found to delay senescence either by increasing the production of ROS scavenging enzymes (through its positive effect on protein synthesis) or directly by scavenging the free radicals (Synkova et al 2006;Lattanzio et al 2006;Liu et al 2016a). Cytokinins have also been found to slow down the process of free radical formation during senescence in tobacco plant (Synkova et al 2006;Ahmad and Tahir 2016b;Dek et al 2017). POD, SOD and CAT activity was found to be modulated by the application of cytokinins for efficient scavenging of the reactive oxygen species (Petit-Paly et al 1999, Mwangi et al 2003Mittler et al 2004;Danilova et al 2017).…”
Section: Changes In the Activity Of Antioxidant Enzymesmentioning
confidence: 99%
“…Recently, Dek reported that there was a decrease in cytokinins and an increase in ABA at postharvest leaves, nevertheless increasing ABA concentration could suppress postharvest senescence [ 19 ]. Phosphatidylinositol 3-kinase (PI3K), a key enzyme of phosphorylating phosphatidylinositol, induced senescence by enhancing ethylene biosynthesis and signaling [ 20 ]. The mitochondrial AAA-protease gene FtSH4 could control the SA synthesis and signaling in senescence via modifying the ROS level and WRKY transcription factors [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Against to this, BAP was highly effective in maintaining a decreased LOX activity in flowers followed by TDZ and KN, which prevented the excessive lipid peroxidation of the membranes as evident from increased MSI values in the tissue samples. The reduced LOX activity resulted in maintenance of adequate phospholipids, proteins and thiols by preventing the seepage of proteases from vacuoles into the cytoplasm (Macnish et al, 2010;Liu et al, 2016a;Dek et al, 2017). Cytokinin mediated enhanced membrane integrity can also be attributed to its involvement in maintenance of high water content, antioxidant system and reduced peroxidation rates in tissues, which are greatly affected by the stresses like senescence (Ahmad et al, 2018;Honig et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Petals with decreased APX activity has been found to show early senescence symptoms in various flowers like daylily, gladiolus and carnation by generation and accumulation of ROS (Mittler et al, 2004;Saeed et al, 2014). Exogenous application of cytokinins effectively reduced the free radical formation in tobacco plant during senescence (Dek et al, 2017). The role of cytokinins in maintaining the ambient levels of antioxidant enzymes for longer vase life of the flowers has also been demonstrated by application of cytokinin oxidase inhibitors in wall flowers (Bartrina et al, 2017).…”
Section: Discussionmentioning
confidence: 99%